Pelatihan Smart Business Online Pada SMA Masehi 1 - Gamayanto, Indra; Wibowo, Sasono; santoso, Dewi agustini; Prayitno, Agus; Kurniadi, Agung; Kustiadi, Kustiadi (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
Global competition demands significant changes, we cannot just stick to what is old without making drastic changes. Problems such as the unavailability of infrastructure and human resources are two problems that can actually be solved by implementing training consistently. In this service, we will use infrastructure that is generally available, such as Blibli, Shopee and others. This has supported students in implementing smart online business. This community service will produce basic knowledge for students about smart online business, how we implement it, create an account for an online business, start opening an online shop for the first time and how students can apply e-marketing. In this community service, we will also be able to raise the motivation of students and teachers to increase entrepreneurship and also their motivation to achieve the future, by providing a big picture of time management and mentoring. These two things are of course very important and will be the next community service at SMA Masehi 1, Semarang